A new sulfonamide-based chemosensor for potential fluorescent detection of Cu2+ and Zn2+ ions. (3rd March 2023) - Amoah, Cephas; Obuah, Collins; Ainooson, Michael Kojo; Hamenu, Louis; Oppong, Anita; Muller, Alfred
Abstract: In recent times, there has been an increased demand in the search for probing materials for numerous substances in the environment such as the detection of metals ions. In this study, a new class of pyrazolyl-sulfonamide derivatives of para -nitroaniline were synthesized following a multistep approach. The ligands and complexes were characterized using NMR spectroscopy, IR spectroscopy, and mass spectrometry. All the compounds C1 –C3 were synthesized in very good yields (85%–92%) and their photo-physical properties measured. All the compounds show fluorescence behaviour with emissions within the UV and far visible range with quantum yields between 7.7% and 25.7%. TD-DFT calculations predictions for the electronic transitions present are in good agreement with experimental observations. Fluorescent probing studies conducted on the compounds show that C1 –C3 were analytically sensitive and possessed significant selectivity towards Cu 2+ (for C3 ) and Zn 2+ (for C1 and C2 ) ions with detection limits between 0.011 and 0.103 mg/L for Cu 2+ ions and 0.002–0.135 mg/L for Zn 2+ ions. Overall, C1 was found to be the most sensitive molecule for the metals studied, having good quantum yield and better selectivity for Zn 2+ ion compared to Cu 2+ . Graphical abstract: Image 1